PENGARUH PENDAMPINGAN MPASI TERHADAP PERTUMBUHAN BERAT BADAN BAYI (Studi Eksperimental pada Bayi Usia 6 hingga 10 Bulan di Desa Kedunguter dan Desa Batu, Wilayah Kerja Puskesmas Karangtengah, Kabupaten Demak) - Yessy Rizki Permatasari; Sri Priyantini; Azizah Retno (PT. Hasba Edukasi Mandiri, 2026)
Background: Inappropriate complementary feeding (CF) practices remain a major contributing factor to impaired weight growth in infants. Objective: This study aimed to determine the effect of complementary feeding assistance on weight gain among infants aged 6 to 10 months in the working area of Karangtengah Primary Health Center, Demak Regency. Methods: A quasi-experimental study with a post-test only control group design was conducted among infants aged 6–10 months who were assigned to intervention and control groups, with three months of complementary feeding assistance and data analyzed using the Mann–Whitney test. Results and Discussion: Infants in the intervention group showed a significantly higher mean weight gain compared to the control group (0.4 kg vs 0.2 kg), indicating that complementary feeding assistance effectively supports infant growth. Conclusion and Recommendation: Complementary feeding assistance has a positive effect on infant weight gain and is recommended to be integrated sustainably into routine maternal and child health services, particularly through community health posts.